ANALISIS KESEHATAN DAN KESELAMATAN KERJA DI PABRIK TAHU PAK SUSILO DI KOTA BATAM - Mahendrawan Maulana, Firgi; Zetli, Sri (Computer Science and Industrial Engineering, 2025)
Pak Susilo Tofu Factory is one of the tofu factories engaged in the UMKM food industry. Tofu processing at Pak Susilo's factory still uses traditional tools and methods with minimal use of electrical energy. The problem that occurred in this study was the lack of knowledge and application of K3 in Pak Susilo's UMKM tofu. There were cases of health disorders and work accidents that occurred in the process of producing tofu so that efforts were needed to identify the risk of hazards and assess the risks. The purpose of this study was to improve occupational health and safety by identifying and assessing the level of risk of health disorders and work accidents and to provide appropriate control measures in the Pak Susilo tofu production process. The method used in this study was HIRA (Hazard Identification and Risk Assessment) to identify and assess the level of risk of hazards for workers at the Pak Susilo tofu factory. From the results of this study, 12 production processes of Mr. Susilo's tofu obtained jobs with a risk level of Extreme Risk (17%) as many as 2 jobs, High Risk (41%) as many as 5 jobs, Moderate Risk (17%) as many as 2 jobs and Low Risk (25%) as many as 3 jobs. The proposal given by 3 K3 experts for risk control to the owner of UMKM tofu Mr. Susilo is through eliminating sources of danger from the workplace, replacing safer tools, risk control measures with tool engineering to reduce potential hazards, reducing the risk of hazards in the workplace by changing policies and equipment that must be used to maintain occupational health and safety, namely PPE.